Good practices on air quality, pollution and health impact at EU level - Daniela-Ioana Manea; Emilia Titan; Mihaela Mihai; Simona Apostu; Valentina Vasile (Amfiteatru Economic Journal, 2020)
The EU's environmental policies and strategies have been developed since the 1970s and underline that the sustainable economic development and well-being of the European Union countries are based on their natural environment. They are aimed at national and global air quality regulations that support the improvement of the air quality and the health of the population. The principal objective of this paper is to highlight the importance of the varied and complex action of the polluting environment on the organism. A convergent objective is the development of pollution management solutions and highlighting good practices for combating and reducing pollution and improving air quality. In this regard, the results of the analysis presented in the paper indicate that a healthier environment can prevent diseases caused by polluted air and decrease the number of deaths caused by respiratory and cardiovascular diseases. This statement represents the main result obtained by applying the methods of multidimensional data analysis (factorial analysis, principal component analysis, cluster analysis) to evaluate the complexity of contemporary environmental and health challenges. On the other hand, the use of tools and examples of the good practices for implementing strategies to improve environmental factors, especially air quality, are particularly useful in creating specific policies that lead to improving the quality of the environment and, implicitly, the health of the population.
Keywords: I15; Q53; Q57; C38; 330; air quality; health; pollution; good practices; multivariate analysis